Cold-Induced Freezing Tolerance in Arabidopsis - Wanner, Leslie A. (American Society of Plant Physiologists, 1999)
Changes in the physiology of plant leaves are correlated with enhanced freezing tolerance and include accumulation of compatible solutes, changes in membrane composition and behavior, and altered gene expression. Some of these changes are required for enhanced freezing tolerance, whereas others are merely consequences of low temperature. In this study we demonstrated that a combination of cold and light is required for enhanced freezing tolerance in Arabidopsis leaves, and this combination is associated with the accumulation of soluble sugars and proline. Sugar accumulation was evident within 2 h after a shift to low temperature, which preceded measured changes in freezing tolerance. In contrast, significant freezing tolerance was attained before the accumulation of proline or major changes in the percentage of dry weight were detected. Many mRNAs also rapidly accumulated in response to low temperature. All of the cold-induced mRNAs that we examined accumulated at low temperature even in the absence of light, when there was no enhancement of freezing tolerance. Thus, the accumulation of these mRNAs is insufficient for cold-induced freezing tolerance.